Single-cell biological network inference using a heterogeneous graph transformer - Anjun Ma; Xiaoying Wang; Jingxian Li; Cankun Wang; Tong Xiao; Yuntao Liu; Hao Cheng; Juexin Wang; Yang Li; Yuzhou Chang; Jinpu Li; Duolin Wang; et al. (Nature Communications, 2023)
Single-cell multi-omics and deep learning could lead to the inference of biological networks across specific cell types. Here, the authors develop DeepMAPS, a deep learning, graph-based approach for cell-type specific network inference from single-cell multi-omics data that is tested on healthy and tumour tissue datasets.